2009
DOI: 10.1080/08870440801975127
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a forgiveness intervention on patients with coronary artery disease

Abstract: This research assesses the effects of a psychology of forgiveness pilot study on anger-recall stress induced changes in myocardial perfusion, forgiveness and related variables. Thirty-two patients were administered baseline rest and anger-recall stress imaging studies, and 17 of these participants who demonstrated anger-recall stress induced myocardial perfusion defects (forgiveness group, n = 9; control group, n = 8) were randomly assigned to a series of 10 weekly interpersonal forgiveness or control therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 59 publications
4
40
1
Order By: Relevance
“…Such relationship repair skills can also reduce the emotional and physical stress that comes with unforgiveness (e.g., Harris et al 2006;Lawler et al 2003;VanOyen Witvliet et al 2001). Randomized controlled intervention studies with adults have shown that forgiveness training can lead to increases in psychological health and decreases in afflictive emotions, rumination, and reactivity (e.g., Baskin and Enright 2004;Harris et al 2006;Luskin et al 2005;Reed and Enright 2006;Waltman et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Such relationship repair skills can also reduce the emotional and physical stress that comes with unforgiveness (e.g., Harris et al 2006;Lawler et al 2003;VanOyen Witvliet et al 2001). Randomized controlled intervention studies with adults have shown that forgiveness training can lead to increases in psychological health and decreases in afflictive emotions, rumination, and reactivity (e.g., Baskin and Enright 2004;Harris et al 2006;Luskin et al 2005;Reed and Enright 2006;Waltman et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Forgiveness is also associated with better physical health and with physiological profiles that underlie good health. In this context, forgiveness predicts fewer physical health symptoms, better overall physical health (Lawler et al, 2005; Seawell et al, 2014), healthier cardiovascular responses to stress (Lawler et al, 2003), and lower rates of cardiovascular disease (Friedberg et al, 2007; Toussaint and Cheadle, 2009b; Waltman et al, 2009). As can be expected, forgiveness is thus also associated with lower rates of mortality (Krause and Hayward, 2013; Toussaint et al, 2012).…”
mentioning
confidence: 99%
“…Forgiveness intervention has been used directly as an effective measure for reducing hostility and health problems for patients with coronary artery disease. In one study, forgiveness intervention therapy proved significantly more effective than conventional psychotherapy in improving outcomes for patients with coronary artery disease (Waltman et al 2009). In another, researchers concluded that forgiveness as a means of reducing hostility was a crucial component (and maybe the most crucial component) in the success of the Recurrent Coronary Prevention Project, a 5-year study designed to improve the health of heart patients by altering Type A personality traits (Friedman et al 1986;Kaplan 1992).…”
Section: The Connection Between Forgiveness Hostility and Healthmentioning
confidence: 97%
“…Forgiveness seems to have protective benefits for patients with heart disease, including a reduced risk of myocardial ischemia and lower total cholesterol to HDL and LDL to HDL ratios among patients with coronary artery disease (Friedberg et al 2009;Waltman et al 2009). Among individuals with spinal cord injuries, those who were more forgiving of others reported greater life satisfaction and better health outcomes (Webb et al 2010).…”
Section: Forgiveness and Healthmentioning
confidence: 99%